Potential Anti-Inflammatory, Anti-pyretic and Anti-Ulcerative Effects of Hexane Fraction of Ardisia Crispa (thumb.) A.DC. - Lau, Moi Fong (2011)
Ardisia crispa has been claimed by local villagers to have medicinal properties, and it is widely used in treating dysmenorrhea, rheumatism, orchitis, skin problem, coughs, fractured bones, sprains and for treatment women afterbirth. This study was conducted to investigate the possible anti-inflammatory and anti-pyretic effects of hexane fraction of A. crispa root (HFAC) in various experimental animal models. For toxicity screening, ACHE at the dose range of 300 - 1800 mgkg-1 was tested to determine its LD50. For antipyretic activity study, brewer’s yeast was injected into mice to induce fever and later, HFAC at dose ranging from 10 to 300 mgkg-1 was administered to the rats orally. For anti-inflammatory activity study, 12-Otetradecanoylphorbol-13-acetate (TPA) was applied to ear of mice to induce oedema and treated with 0.5, 1 and 2 mgmL-1 of HFAC topically. Cotton-pellet-induce granuloma in sub chronic study, treated groups have received 3, 10, 30 and 100 mgkg-1 of HFAC administered orally for 7 days. Then pellets are dissected out and weighed. For anti-arthritic activity study, Complete Freund’s adjuvant (CFA) was injected onto plantar aponeurosis of right paw of rat to induce chronic arthritis. The following day onwards, HFAC at 3, 10, 30, and 100 mgkg-1, and indomethacin were administered to the rats. Paw volume of rat was measured with a plethysmometer for 14 days. Ankle tissue was collected for ELISA test of tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β). In anti-ulcerogenic study, the rats were divided into 3 groups: L-NAME pre-treatment group, NEM-pretreatment group and saline pre-treatment group. Each group has 6 sub-groups with 6 animals were fasted for 48 hours with free access of water. Groups were orally administrated with 1 ml absolute ethanol to induce ulcer. One hour after ethanol administration, animals were sacrificed by cervical dislocation and stomach was removed to determine the ulcer lesion areas and photographs were taken. The stomach biopsies were kept in 10% formalin for histological analysis. The LD50 of HFAC was 836.12 mgkg-1. Results obtained showed that HFAC showed significant anti-pyretic effect at all doses (10, 30, 100 and 300 mgkg-1). At 30, 100 and 300mgkg-1, HFAC exhibited even higher efficacy when compared with 100 mg/kg acetaminophen. In TPA induced ear oedema model, 1 and 2 mg/ear of HFAC produced significant suppression by 19.9%and 20.2% of ear oedema, respectively. HFAC also elicited a significant (P<0.05)inhibition of granuloma tissue and exudate formation in cotton-pellet induced granuloma. The result exhibited that HFAC at all doses (3, 10, 30 and 100 mgkg-1)have significant (p<0.05) inhibition of oedema of 45.3%, 64.3%, 73.1% and 49.6%, respectively. In arthritic model, during the first phase after CFA-injection, oedema was increased and then reduced at 4 days after. The second onset of action started at day 9 for certain doses of HFAC treated groups (10 and 30 mgkg-1) and indomethacin. At 3, 10 and 30 mgkg-1, HFAC significantly reduced TNF-α by 45.2%, 45.7% and 25.1%, respectively when compared with control. For IL-1β, only 10 mgkg-1 and 30 mgkg-1 of HFAC elicited a significant (p<0.05) inhibition of this mediator in local tissue by 45.9% and 36.5%, respectively. The efficacies of those doses were comparable to the effect of indomethacin (34.6%). The gastroprotective effect of HFAC was observed in the groups pre-treated with L-NAME, which was very similar to cytoprotective response on lesion induced in pre-treatment saline groups. At 30, 100, and 300 mgkg-1 HFAC exhibited its cytoprotective effect by 95.6%, 99.3% and 99.1% respectively. At 30 and 100mgkg-1, animals pre-treated with saline received HFAC, have exhibited reduction in gastric lesion by 95.6% and 99.3% compared to NEM pre-treatment group (57.1% and 52.6%) and thus it showed significant gastroprotection (p<0.001). At 300 mgkg-1 with saline pre-treated group,HFAC significantly suppressed the gastric lesion (p< 0.05) by 99.1% when compared to NEM group (69.9%). Thus, HFAC may possess anti-ulcerogenic effect via SH group. In histological analysis, all doses of HFAC treated in NEM pre-treated animals at 10 mgkg-1, 30 mgkg-1, 100 mgkg-1 and 300 mgkg-1 have shown a significant increase in the mean score of haemorrhage and blood congestion features (p<0.05) indicating the attenuation of ulcer inhibition in NEM pretreated group.Thus,based on the results of the present studies, it can be concluded that A. crispa possesses anti-inflammatory, antipyretic and anti-ulcerogenic effect in rats and this may possibly due to the flavonoid and triterpenoid content in HFAC. However,further studies should be done to determine the exact mechanisms underlying those pharmacological effects especially in the fraction’s bioactive compounds.